Obesity and Its Co-Morbidities among School Teachers in Dhaka City (KYAMC Journal, 2023)
Background: Obesity is an important cause for human morbidity and mortality. Objective: This study was aimed to determine the prevalence of obesity and its co-morbidities among school teachers in Dhaka city. Materials and Methods: This cross sectional study was carried out from May 2017 to October of 2017. Total 250 school teachers aged between 25-59 years were enrolled using cluster random sampling technique. Data on socio-demographic profile, co-morbidities, weight, height and blood pressure were recorded. Results: The prevalence of obesity among school teachers was 15.2%. The mean age of the participants was 46.1±8.2 years. Female teachers were more obese compared to male (20% vs 5.9%), this association was statistically significant (p=0.001). Majority obese participants belonging to the age group of 41-59 years with higher prevalence among female compared to male (25.2% vs 5.8%), this was statistically significant (p=0.030). About 53% obese teachers had hypertension (HTN). On the other hand, Pre-HTN was observed more among obese participants (42.1%) compared to overweight (14.8%). About one third of overweight and obese participants were diabetic (30.6% and 34.2% respectively) and dyslipidaemic (21.5% and 23.7% respectively). Conclusion: The prevalence of obesity and its co-morbidities such as HTN, diabetes mellitus (DM), dyslipidaemia etc was high among the study participants. By promoting healthy life style and behaviors can reduce the burden of obesity and its co-morbidities.KYAMC Journal Vol. 13, No. 04, January 2023: 245-249